Analysis of the Influence of Safety Culture on Employee Work Behavior to Improve Operational Performance in a Machinery Repair Service Company - Muhammad Chairuddin Widad; Muhamad Abdul Jumali (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Increasing competition in the machinery repair service industry requires companies to improve operational performance through effective human resource management. One important factor contributing to operational excellence is the implementation of a strong safety culture, which promotes disciplined work behavior, improves compliance with operational procedures, and enhances business performance. This study aims to analyze the effect of safety culture implementation on employee work behavior to improve operational performance in a machinery repair service company in Jakarta. A quantitative survey was conducted involving 30 employees selected using a total sampling technique. Data were collected through questionnaires and analyzed using simple linear regression. The results indicate that safety culture has a positive and significant effect on employee work behavior with a regression coefficient of 0.490, a t-value of 5.063, a significance value of 0.000 (<0.05), and a coefficient of determination (R²) of 47.8%. As a practical implication, a Job Safety Analysis (JSA) was developed for the Rewinding Electro Motor process to support work standardization and improve the company's operational performance.